Experiment at KwaPoyinandi: African Engagement with the Local Health Commission of the Edendale and District Public Health Area, 1942–c.1957. Issue 2 (3rd April 2022) - Epprecht, Marc
ABSTRACT: KwaPoyinandi was the Zulu term for the Local Health Commission (LHC), a unique but now little-remembered form of local authority that governed the freehold community of Edendale and contiguous farms, townships, and informal settlements from 1942 to 1974. Its early mandate was to rehabilitate the once prosperous community within the social medicine paradigm (primary health care attentive to the social determinants of health) and with the promise of transition to self-governance. Through to the late 1950s, 'monumental work' toward that mandate was achieved, including a multiracial advisory board with an African majority and an African chair. KwaPoyinandi also bucked the national apartheid trend for longer than most, if not all, major urban centres in South Africa, with a racially diverse population well into the 1970s. The experiment was hamstrung and ultimately shut down due to its incompatibility with apartheid. I argue that Africans' active engagement with KwaPoyinandi in diverse and complex ways was an important factor in its early relative success and that this history provides insights pertinent to current debates around the revitalisation of peri-urban communities around South Africa.